Determination of Milk Composition, Bacteriology and Selected Blood Parameters of Dairy Goats Under Different Feeding Systems - Degirmencioglu, Taskin; Goncagul, Gulsen; Ozbilgin, Selda; Gocmen, Huban (Animal Review, 2016)
This research was carried out at two farms located in the Karacabey region of Turkey: an extensive goat farm (A) and a semi-intensive goat farm (B). A total of 32 Saanen goats (3 years old) at an early stage of their second lactation were selected from Farm A and Farm B. The total DM intake (TDM) values were 1.89 and 1.86 (kg d-1) for goats housed on the A and B farms, respectively. Compared with Farm A, Farm B produced more milk each day (P<0.05; 1.38 -. 1.76 kg day-1). The milk samples taken from Farm A had a higher (P<0.05) milk fat content than the samples from Farm B (milk fat=4.40 and 1.89 %, respectively). The serum creatinine values were significantly higher (P<0.05) in the blood of goats from farm A compared with farm B (1.11 and 0.56 mg dl-1, respectively). Comparison of glucose levels from both farms showed a significantly higher level of glucose in the blood samples from goats at Farm B (P<0.05; 24.23 and 61.43 mg dl-1). Serum parameters for cholesterol, GGT and urea were not affected by the feeding system (P > 0.05).